OTU-001 Identification of a novel therapeutic agent for treating IBD guided by systems medicine. (8th June 2018) - Burkitt, Michael; Lloyd, Kate; Papoutsopoulou, Stamatia; Smith, Emily; Stegmaier, Philip; Mark Pritchard, D; Kel, Alexander; Müller, Werner; Probert, Chris
Abstract : Introduction: There remains an unmet need in the treatment of IBD. The SysmedIBD project established a multi-disciplinary consortium to systematically investigate patients with inflammatory bowel disease, focusing on the dynamics of NF-κB signalling. Through this approach we identified an established drug with potential for repurposing to treat IBD, in selected patients. Methods: Novel targets with potential for impacting outcomes of IBD were identified in-silico by combining integrated promoter/pathway analysis of published microarray data and systematic text-mining of the published literature using the geneXplain software platform. An established drug with potential for repurposing was assessed as a proof-of-concept agent using a multi-step validation pipeline based on its effect on NF-κB dynamics in-vitro and in-vivo, and its ability to ameliorate murine experimental colitis. Results: 3191 pharmacological agents (Prestwick Chemical Library) were assessed in-silico . 36 agents were highly significantly predicted to influence NF-κB and other IBD target activity. Amongst the highest ranked agents were the macrolide antibiotics. Clarithromycin (CLA) was selected as a paradigm for subsequent analyses. The effects of CLA were investigated in 5 experiments: NF–κB mediated transcription was investigated using peritoneal macrophages and enteric organoids from a mouse expressing firefly luciferase under the control of the human TNF promoter: CLA suppressed responses in both tissues (p<0.05). NF–κB(p65) protein shuttling dynamics were characterised in enteric organoids cultured from a mouse expressing human p65–dsRed: CLA suppressed TNF induced oscillation of p65 (p=0.0002). C57BL/6 mice were treated with intra–peritoneal LPS (0.125 mg/kg) to induce small intestinal NF–κB activation: CLA suppressed DNA binding of p65 (p=0.002). The effect of CLA on DSS colitis was studied: mice treated with CLA lost significantly less weight (p<0.05), and had less severe histology than mice treated with vehicle (p=0.004). The effect of CLA on TNF induced nuclear localisation of p65 in human enteric organoids was studied: CLA suppressed p65 nuclear localisation (p<0.0001). Conclusions: Using a systems biology approach, we have identified an agent with potential for repurposing to treat IBD. Outcomes of earlier clinical trials of clarithromycin were discordant: we are developing a biomarker of NF-κB responsiveness that may enable precise selection of patients for a personalised medicine trial.